Sol's geese - Lynch, Gay; Tilders, Loma (Macmillan South Yarra, Vic., 1998)
Sol's Geese by Gay Lynch is a heartwarming children$1 (Bs book that tells the story of a young boy named Sol and his beloved geese. As Sol cares for the geese, he learns important life lessons about responsibility, friendship, and the beauty of nature. The narrative captures Sol$1 (Bs adventures with his feathered friends, highlighting the bond they share and the challenges they face together. Through vivid illustrations and charming storytelling, the book celebrates themes of connection, compassion, and the joys of rural life, making it an engaging read for young audiences who love animals and the outdoors.s